093 Cardiac involvement in cardiac al amyloidosis as measured by equilibrium contrast cardiovascular magnetic resonance. (16th May 2012) - Banypersad, S M; Sado, D; Flett, A S; Gibbs, S; Pinney, J; Maestrini, V; Wechalekar, A; Hawkins, P N; Moon, J C
Abstract : Introduction: Cardiac involvement drives prognosis in Systemic AL Amyloidosis, predicting outcome and influencing therapeutic options. Current methods of cardiac assessment do not quantify the myocardial amyloid burden. We used Equilibrium Contrast Cardiovascular Magnetic Resonance (EQ-CMR) to measure the cardiac interstitial compartment, measured as the myocardial contrast volume of distribution, Vdm, which we hypothesised would reflect the amyloid burden. Methods: Patients with systemic AL amyloidosis undergoing routine work up at the National Amyloidosis Centre were recruited (n=60, 39 males, 21 females, mean age 63 years) and underwent conventional CMR including late enhancement, EQ-CMR to measure Vdm and standard cardiac work-up including ECG, echocardiography, biomarkers (BNP, Troponin T) and functional assessment (6-min walk test, 6MWT, where permitted by autonomic neuropathy). Results were compared to normal controls. Conventional assessment ranked cardiac involvement as definite, probable and none. Results: Vdm was significantly higher in patients than normal controls (0.25 vs 0.40, p<0.001) (see Abstract 093 figure 1A ). This tracked conventional cardiac assessment (none, probable, definite corresponded with a Vdm of 0.276 vs 0.342 vs 0.488, p<0.005), respectively (see Abstract 093 figure 1B ). Vdm correlated with cardiac parameters by echo (eg, TDI S-wave R 2 0.27, p<0.001) and conventional CMR (eg, indexed LV mass R 2 0.31, p<0.001—see Abstract 093 figure 2 ). Significant correlations were also seen with BNP (R 2 0.47, p<0.001) and Troponin T (R 2 0.28, p=0.006). Vdm was associated with ECG abnormalities and tracked small QRS voltages (R 2 0.33, p<0.001). A higher Vdm correlated with a lower 6MWT outcome (R 2 0.13, p=0.03). Conclusions: The measurement of the myocardial interstitial compartment (Vdm ) using EQ-CMR in systemic AL amyloidosis quantifies the cardiac amyloid burden.